Longitudinal egg‐specific regulatory T‐ and B‐cell development: Insights from primary prevention clinical trials examining the timing of egg introduction. Issue 5 (29th October 2020) - Lai, Catherine L.; Campbell, Dianne E.; Palmer, Debra J.; Makrides, Maria; Santner‐Nanan, Brigitte; Gold, Michael; Tan, John Wei‐Liang; Valerio, Carol; Nanan, Ralph; Prescott, Susan L.; Hsu, Peter S.
Abstract: Background: Egg allergy affects almost 1 in 10 Australian infants. Early egg introduction has been associated with a reduced risk in developing egg allergy; however, the immune mechanisms underlying this protection remain unclear. Objective: To examine the role of regulatory immune cells in tolerance induction during early egg introduction. Methods: Cryopreserved peripheral blood mononuclear cells (PBMC) were obtained from infants from 2 randomized controlled trials of early introduction of egg for the primary prevention of egg allergy; BEAT (at 12 months, n = 42) and STEP (at 5 months n = 82; 12 months n = 82) study cohorts. In vitro ovalbumin‐stimulated PBMC were analyzed by flow cytometry for presence of ovalbumin‐specific regulatory T cells, using activation markers, FoxP3, and IL‐10 expression. Ovalbumin‐specific regulatory B cells were identified by co‐expression of fluorescence‐conjugated ovalbumin and IL‐10. Results: Specific, age‐dependent expansion of ovalbumin‐specific regulatory T cells was only observed in infants who (a) had early egg introduction and (b) did not have egg allergy at 12 months. This expansion was blunted or impaired in children who did not undergo early egg introduction and in those with clinical egg allergy at 12 months. Infants with egg allergy at 12 months of age also had reduced frequency of ovalbumin‐specific regulatory B cells compared to egg‐tolerant infants. Conclusion: Early egg introduction and clinical tolerance to egg were associated with expansion of ovalbumin‐specific T and B regulatory cells, which may be an important developmental process for tolerance acquisition to food allergens. Abstract : Early egg consumption in infants is associated with expansion of ovalbumin‐specific Tregs over time. Egg allergic infants had blunted expansion of ovalbumin‐specific Tregs and lower ovalbumin‐specific Bregs compared to those not egg allergic. Early egg consumption was associated with increased egg‐specific IgG4, which correlated with IL‐10 producing ovalbumin‐specific Treg in non‐egg allergic infants. Abbreviations: BEAT, Beating Egg Allergy Trial; OVA, ovalbumin; STEP, Start Time of Egg Protein to Prevent Egg Allergy